Individualized Out-of-Pocket Price Estimators for “Shoppable” Surgical Procedures: A Nationwide Cross-Sectional Study of US Hospitals - Nicholas L. Berlin, MD, MPH, MS; Zoey Chopra, BA; Arrice Bryant, MD, MPH; Josh Agius; Simone R. Singh, PhD; Karan R. Chhabra, MD, MS; Paul Schulz, MA; Brady T. West, PhD; Andrew M. Ryan, PhD; Jeffrey T. Kullgren, MD, MS, MPH (Annals of Surgery Open, 2022)
Objective:. To estimate the nationwide prevalence of individualized out-of-pocket (OOP) price estimators at US hospitals, characterize patterns of inclusion of 14 specified “shoppable” surgical procedures, and determine hospital-level characteristics associated with estimators that include surgical procedures. Background:. Price transparency for shoppable surgical services is a key requirement of several recent federal policies, yet the extent to which hospitals provide online OOP price estimators remains unknown. Methods:. We reviewed a stratified random sample of 485 U.S. hospitals for the presence of a tool to allow patients to estimate individualized OOP expenses for healthcare services. We compared characteristics of hospitals that did and did not offer online price estimators and performed multivariable modeling to identify facility-level predictors of hospitals offering price estimator with and without surgical procedures. Results:. Nearly two-thirds (66.0%) of hospitals in the final sample (95% confidence interval 61.6%–70.1%) offered an online tool for estimating OOP healthcare expenses. Approximately 58.5% of hospitals included at least one shoppable surgical procedure while around 6.6% of hospitals included all 14 surgical procedures. The most common price reported was laparoscopic cholecystectomy (55.1%), and the least common was recurrent cataract removal (20.0%). Inclusion of surgical procedures varied by total annual surgical volume and health system membership. Only 26.9% of estimators explicitly included professional fees. Conclusions:. Our findings highlight an ongoing progress in price transparency, as well as key areas for improvement in future policies to help patients make more financially informed decisions about their surgical care.